An attack on N = p2q with partially known bits on the multiple of the prime factors - Wan Mohd Ruzai, Wan Nur Aqlili (Universiti Putra Malaysia, 2021)
This paper presents a cryptanalytic study upon the modulus N = p 2q consisting of two large primes that are in the same-bit size. In this work, we show that the modulus N is factorable if e satisfies the Diophantine equation of the form ed − k(N − (ap)2 − apbq + ap) = 1 where ab is an unknown approximation of qp. Our attack is feasible when some amount of Least Significant Bits (LSBs) of ap and bq is known. By utilising the Jochemsz-May strategy as our main method, we manage to prove that the modulus N can be factored in polynomial time under certain specified conditions.